Earthquake history at the eastern boundary of the South Taupo Volcanic Zone, New Zealand. Issue 4 (1st October 2016) - Gómez-Vasconcelos, MG; Villamor, P; Cronin, SJ; Procter, J; Kereszturi, G; Palmer, A; Townsend, D; Leonard, G; Berryman, K; Ashraf, S
ABSTRACT: At the eastern boundary of the south Taupo Rift, the NE-striking, rift-bounding Rangipo and the ENE-striking Wahianoa active normal faults intersect. We investigate their intersection at the Upper Waikato Stream to understand the kinematics of a rift termination in an active volcanic area. The Upper Waikato Stream Fault is a previously unrecognised seismogenic source also at the eastern boundary, capable of producing a M W 6.5 and up to M W 7.1 earthquake if it ruptures in conjunction with the Rangipo or Wahianoa faults. We found a minimum of 12 surface-rupturing earthquakes in the last 45.16 ka on the Upper Waikato Stream Fault (mean slip-rate c. 0.5 mm/yr), and a minimum of nine surface-rupturing earthquakes in the last 133 ka on the Wahianoa Fault (mean slip-rate c. 0.2 mm/yr). Periods of highest slip-rate on these faults may coincide in time with Taupo, Ruapehu or Tongariro eruptions, but, despite their intersection, movement was not coincident across all faults. The Upper Waikato Stream Fault responded to a major Taupo Volcano eruption, the Wahianoa to a major eruptive sequence from Mt Tongariro and the Rangipo to major explosive events from Mt Ruapehu.